2020
DOI: 10.1021/jacs.0c03353
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Acceleration of Cogwheel Helical Self-Organization of Dendronized Perylene Bisimides by the Dendron Sequence Encoding Their Tertiary Structure

Abstract: The cogwheel model of hierarchical self-organization provides a route to highly ordered crystalline helical columnar hexagonal arrays of perylene bisimides (PBIs) conjugated to (3,4,5)dimethyloctyl (racemic dm8*, r) minidendrons. Cogwheel PBIs assemble with identical structural order irrespective of molecular chirality to generate helical columns jacketed with an alkyl coat with length equal to half the helical pitch, exhibiting helical deracemization in the crystal state. These assemblies were accessible only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 113 publications
0
22
0
Order By: Relevance
“…For example, Fenniri and co-workers prepared bicyclic self-pairing molecules that form supramolecular polymers of planar, stacked hexads in solution but crystallize as nonplanar, unstacked hexads . In contrast, X-ray fiber diffraction (XRFD) provides a powerful tool for structural analysis that can preserve the linear, polymeric nature of supramolecular assemblies. This technique has been successfully applied to supramolecular hydrogels for determining the unit cell dimensions and to confirm self-sorting in two-component supramolecular gels. …”
Section: Introductionmentioning
confidence: 99%
“…For example, Fenniri and co-workers prepared bicyclic self-pairing molecules that form supramolecular polymers of planar, stacked hexads in solution but crystallize as nonplanar, unstacked hexads . In contrast, X-ray fiber diffraction (XRFD) provides a powerful tool for structural analysis that can preserve the linear, polymeric nature of supramolecular assemblies. This technique has been successfully applied to supramolecular hydrogels for determining the unit cell dimensions and to confirm self-sorting in two-component supramolecular gels. …”
Section: Introductionmentioning
confidence: 99%
“…This dynamics revealed different communication mechanisms between components in both covalent and supramolecular copolymers. Therefore, different chiral amplification or chiral enhancement effects such as sergeants and soldiers, majority rules, chiral coalition, chiral accord, and chiral conflict have been observed. As a consequence, the common properties presented by these polymers have allowed the development of materials combining these two structural motifs. Regarding the helical sense induction mechanism, some research groups have demonstrated the efficient long-distance transmission of chiral information for poly­(isocyanide)­s, , poly­(vinylterphenylene)­s, , and poly­(acetylene)­s. Recently, our group has reported on poly­[oligo­( p -phenyleneethynylene)­acetylene]­s (POPEPAs), a novel family of helical polymers . In these polymers, even though the chiral center is placed at a remote position from the backbone, a helix induction occurs due to the chiral arrangement of the achiral spacers, which is harvested by the polyene backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Another remarkable result was provided by the self-assembling dendron V d with X = −CO 2 CH 3 , the less ordered V d with X = −CH 2 OH, and the disordered V d with X = −COOH from Table . V d with X = −CO 2 CH 3 self-organizes into a highly ordered helical column by principles resembling those of tobacco mosaic virus (TMV). ,, This self-assembly process will be discussed in a different subchapter together with the mechanisms of lamellar and BCC self-organizations.…”
Section: Resultsmentioning
confidence: 99%
“…The original self-assembling compounds were constructed from benzyl ether dendrons functionalized with aliphatic, fluorinated, semifluorinated, and oligooxyethylene fragments , and subsequently were expanded to other constructs to be discussed in more detail later. They led to the immediate discovery of helical self-organizations, Frank–Kasper phases, and soft quasicrystals that were subsequently found in many other forms of soft matter such as block copolymers, lipids, surfactants, giant molecules, and DNA-grafted nanoparticles. More recently they evolved in biological membrane mimics and into a single component delivery system for mRNA . The dream of self-organized complex soft matter is to reach the perfection of periodic arrays self-organized from inorganic materials that are assembled from a small number of atoms as well as that of biological macromolecules that is self-organized from millions of atoms.…”
Section: Introductionmentioning
confidence: 99%